Silver‐Free Au(I) Catalysis Enabled by Bifunctional Urea‐ and Squaramide‐Phosphine Ligands via H‐Bonding. Issue 46 (28th June 2021) - Franchino, Allegra; Martí, Àlex; Nejrotti, Stefano; Echavarren, Antonio M.
Abstract: A library of gold(I) chloride complexes with phosphine ligands incorporating pendant (thio)urea and squaramide H‐bond donors was prepared with the aim of promoting chloride abstraction from Au(I) via H‐bonding. In the absence of silver additives, complexes bearing squaramides and trifluoromethylated aromatic ureas displayed good catalytic activity in the cyclization of N ‐propargyl benzamides, as well as in a 1, 6‐enyne cycloisomerization, a tandem cyclization‐indole addition reaction and the hydrohydrazination of phenylacetylene. Kinetic studies and DFT calculations indicate that the energetic span of the reaction is accounted by both the chloride abstraction step, facilitated by the bidentate H‐bond donor via an associative mechanism, and the subsequent cyclization step. Abstract : Gold(I) chloride complexes with bifunctional phosphino(thio)urea and phosphinosquaramide ligands have been designed to be catalytically active in the absence of silver additives in intra‐ and intermolecular reactions of alkynes. Structure‐activity relationships, DFT calculations focused on the Au−Cl bond activation, and comprehensive kinetic studies highlight the key role of the H‐bond donor group in enabling catalysis at the Au(I) center.